Developing competent youth and strong communities through after-school programming - Danish, Steven J.; Gullotta, Thomas P. (CWLA Press, 2000)
This collection of essays on the promotion of youth social competency through after-school programming represents the scholarship of a select group of individuals chosen in some cases for their skilled practice experiences and in other instances for their academic scholarship in this area. This unique group of practitioners and scholars represents the third class of Gimbel Child and Family Scholars. For nearly a decade, the Gimbel Foundation has supported Child and Family Agency of Southeastern Connecticut in the funding of this program. Through independent study and two meetings over two long weekends, the authors of the chapters in this book sought to strengthen their programs and their knowledge in a learning community devoted to exploring ways in which young people's lives can be enriched and personal competencies developed. In this book, readers will find a starting point for their own work toward developing quality after-school programming for youth.